(untitled) (Nigerian Dental Journal, 2025)
Background: Surgical resection is the primary treatment for ameloblastoma but often causes facial disfigurement and complications. Conservative management of unicystic ameloblastoma (UA) may prevent these issues. Clinicians should note that combining marsupialization, enucleation, and Carnoys solution adjuvant therapy restores jawbone health, prevents complications, and improves patients quality of life. Presentation: Two pediatric casesa 13-year-old boy with a 3-month right mandibular ramus swelling and an 11-year-old boy with a 5-month anterior mandibular swellingpresented at General Hospital Ifako-Ijaiye. Clinical and investigative findings confirmed unicystic mural ameloblastoma. Intervention: Both underwent marsupialization followed by enucleation with Carnoys solution. Preoperative orthopantomograms showed unilocular radiolucent lesions; postoperative imaging revealed restored bony trabeculae. Outcome: Successful treatment with no recurrence after one year (ongoing monitoring). There was no clinical or radiographic evidence of recurrence at 1-year follow-up. Planned surveillance per IAOMS guidelines (≥5 years for mural UA)" Conclusion: Conservative UA management with regular follow-up prevents facial disfigurement and complications associated with resection, improving quality of life. These are Nigeria’s first documented pediatric UA cases. Keywords: unicystic ameloblastoma, marsupialization, enucleation, Carnoys solution.